Improving frequency response for AC interconnected microgrids containing renewable energy resources - Elshenawy, Mahmoud; Fahmy, Ashraf; Elsamahy, Adel; El Zoghby, Helmy M.; Kandil, Shaimaa A. (Frontiers in Energy Research, 2022)
Interconnecting two or more microgrids can help improve power system performance under changing operational circumstances by providing mutual and bidirectional power assistance. This study proposes two interconnected AC microgrids based on three renewable energy sources (wind, solar, and biogas). The wind turbine powers a permanent magnet synchronous generator. A solar photovoltaic system with an appropriate inverter has been installed. In the biogas Generator, a biogas engine is connected to a synchronous generator. M1 and M2, two interconnected AC microgrids, are investigated in this study. M2 is connected to a diesel engine, which provides constant power. The distribution power loss of interconnected AC microgrids are modelled as Objective Functions (OF). Minimizing this OF will result in optimal power flow in microgrids. This research also created a unique frequency control method called Virtual Inertia Control (VIC), which stabilizes the microgrid frequency using an optimal controller. In this paper, the following five controllers have been studied: proportional integral controller (PI), fractional order PI controller (FOPI), fuzzy PI controller (FPI), fuzzy fractional order PI controller (FFOPI) and VIC based on FFOPI controller. The five controllers are tuned using Particle Swarm Optimization (PSO) to minimize the (OF). At step load disturbances, and eventually grid following/forming contingencies, simulation results are recorded using the MATLABTM platform.